Tromsø som samisk by? – Språkideologier og medienes rolle i språkdebatten - Hiss, Florian (Nordlit, 2012)
This article presents a critical analysis of the discursive practices in the public debate on Sámi language in Tromsø. The conflict around the political plan of Tromsø municipality to join the administrative area for the Sámi language lasted for about one year and was largely  carried out in  the  local  newspapers,  which  had  established  themselves  as  an arena and broker in the conflict. The focus of this study is, on the one hand, on the role of the media in the debate and, on the other hand, on the socially constructed relations between Sámi and Norwegian language and social meanings, which get expressed in a highly  ideological  picture of  language  and  local  identity  and  form  the  ground  for the language conflict. The analytic strategy is twofold: as a first step, the study focuses on the reproduction of  language  ideologies  in  letters  to  the  editor  and readers’  contributions  to  the  local papers’  discussion  pages.  The identification  of  the  three  semiotic  processes  of iconization (rhematization),  fractal  recursivity,  and  erasure  reveals  how  the writers’ expressions of opinion are anchored in a language ideology that connects Sámi language with  certain  social  values  and  ignores  a larger  linguistic  and  cultural  diversity  in  the town of Tromsø. As a second step, the analysis explores the journalistic treatment of the multitude of conflicting voices in the debate and critically sheds light on the construction of a journalistic voice. Although the journalists claim to construe a seemingly neutral ground for their reports (or independent comments), the analysis shows that journalists use  the  representation of  various  voices  in  their  texts  to  construe  a positioned, evaluating, and  ideologically  anchored  journalistic  voice.  In  face  of  the  highly ideological character of the language debate in Tromsø, I argue that local journalism has failed in countering the ideological picture of language and society through information and independent journalism.